Videos on YouTube, Bilibili, TikTok as sources of medical information on Hashimoto’s thyroiditis - Wang, Shiqi; Jia, Siyu; Su, Yanjun; Cheng, Ruochuan (Frontiers in Public Health, 2025)
IntroductionHashimoto’s thyroiditis (HT), a common autoimmune thyroid disorder, is widely discussed on video-sharing platforms. However, user-generated content about HT lacks systematic scientific validation. This study evaluates the reliability and quality of HT-related videos on three major social media platforms: YouTube, Bilibili, and TikTok.MethodsBetween December 1, 10, 2024, the top 200 videos meeting the criteria retrieved under default search settings using a newly registered user account were included for each platform. These videos were from 107 YouTube accounts, 56 Bilibili accounts and 90 TikTok accounts. Metrics including video parameters and creator profiles were recorded. Content quality was evaluated using five validated assessment tools: PEMAT (Patient Education Materials Assessment Tool), VIQI (Video Information and Quality Index), GQS (Global Quality Score), mDISCERN (modified DISCERN), and JAMA (Journal of the American Medical Association) standards.ResultsTikTok videos showed the highest audience engagement. YouTube had more team-based accounts (43.9%), while TikTok and Bilibili predominantly featured individual accounts, with TikTok featuring a notably higher proportion of verified individual accounts (86.7%). Solo narration was the most common video style across YouTube (62.5%) and TikTok (70.0%), while in Bilibili, it was the medical scenario. In contrast, YouTube and Bilibili offered a broader range of content, including TV programs, documentaries, and educational courses. The varying emphases of different assessment tools rendered it difficult to determine which platform boasts the highest content quality, but the video quality scores across all platforms are not satisfying. Additionally, we found that content produced by verified creators was of higher quality compared to that of unverified creators, with this trend being particularly evident among individual accounts.ConclusionSocial media platforms provide partial support for the dissemination of health information about HT, but the overall video quality remains suboptimal. We recommend that professional creators pursue platform certification to enhance the dissemination of high-quality HT-related videos.